Tin-based alloy preformed soldering lug and preparation method thereof
By combining a copper fiber reinforced skeleton with gradient density distribution and a multilayer tin-based paste, the problem of simultaneously controlling the structural stiffness and local compositional function of tin-based alloy preformed sheets in the prior art has been solved, realizing a preformed sheet with integrated performance and improving the overall integrity and impact resistance of the material.
Patent Information
- Application Number
- CN202511497728.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-20
- Publication Date
- 2025-11-25
AI Technical Summary
Existing technologies make it difficult to achieve independent control of structural stiffness and local component function in tin-based alloy preforms, resulting in overall performance that cannot meet high-performance requirements.
A copper fiber reinforced skeleton with gradient density distribution is used, and a hollow gap is formed by weaving process. Combined with tin-based slurry with different composition to form a gradient structure, including an outer layer of tin-antimony-copper-nickel, an intermediate layer of tin-antimony-copper and an inner layer of tin-antimony-copper rare earth, the structure is compressed and post-processed to achieve a continuous transition of composition and performance.
It enhances the integrity, impact resistance, and bonding strength of the material, avoids the interlayer delamination problem caused by abrupt changes in interface properties of multi-layer materials, and realizes a preformed welding sheet with integrated performance.
Smart Images

Figure CN121004381A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of soldering, in particular to a tin-based alloy preformed soldering sheet and a preparation method thereof. BACKGROUND
[0002] With the development of electronic products towards high density, miniaturization and high power, reliable interconnection materials play an increasingly important role in the fields of semiconductor packaging, power devices, automotive electronics, aerospace and high-end consumer electronics. Tin-based alloy, as a commonly used fusible solder, is widely used in surface mount technology (SMT), chip-level packaging, power module welding and heat dissipation structure connection, etc. Especially in high-reliability applications that require consideration of heat conduction, heat dissipation, mechanical support and long-term thermal cycle reliability, preformed soldering sheet, with its precise volume control, repeatability and ease of automated assembly, has become a common solution to ensure soldering quality, reduce voids and improve consistency.
[0003] In the prior art, common practices include using solder paste printing and reflow, metal sheet / preformed solid solder, powder metallurgy or mixing inorganic reinforcing phases into tin-based materials to improve mechanical or thermal conductivity. These methods usually pursue optimization in one direction in terms of material composition - for example, improving melting point, interface reaction or microstructure by alloying (adding antimony, copper, nickel or rare earths), or improving load bearing capacity and thermal conductivity by adding fibers / particles. However, such single-directional modification is difficult to achieve independent control of structural stiffness (mechanical support) and local component function (such as interface reaction control, microstructure refinement, and melting behavior regulation) in spatial scale.
[0004] In view of this, the prior art has relatively single performance in the same preformed body, and the whole cannot meet the technical problem of high performance requirement. SUMMARY
[0005] The purpose of the present application is to provide a tin-based alloy preformed soldering sheet and a preparation method thereof, which solves the above technical problems.
[0006] To achieve this purpose, the present application adopts the following technical solutions: A preparation method of a tin-based alloy preformed soldering sheet, comprising the following steps: Preparation of a copper fiber reinforced skeleton with gradient density distribution, the copper fiber reinforced skeleton comprising a high density region and a low density region, and a hollow gap formed by a weaving process; An outer layer slurry with tin-antimony-copper-nickel as the main body, an intermediate layer slurry with tin-antimony-copper as the matrix, and an inner layer slurry with tin-antimony-copper-rare earth as the matrix, tin-based slurry with different components and functions is prepared, and the three kinds of tin-based slurry are sequentially filled into the preset region of the hollow gap of the reinforced skeleton to form a gradient structure material; The gradient structure material is compression molded and post-processed to obtain a pre-formed solder.
[0007] Optionally, the specific composition of the outer layer slurry is: 60-70% tin, 12-14% antimony, 6-8% copper, 1-2% nickel, and 0.5-1.5% nano-alumina.
[0008] Optionally, the specific composition of the intermediate layer slurry is: 75-82% tin, 8-10% antimony, 4-5% copper, and 0.5-1% nickel.
[0009] Optionally, the specific composition of the inner layer slurry is: 80-87% tin, 6-8% antimony, and 3-4% copper.
[0010] Optionally, the specific process for preparing a copper fiber reinforced skeleton with a gradient density distribution is as follows: Prepare copper fiber raw materials of different diameters and clean and roughen the surface of the pure copper fiber raw materials; Use a multi-arm braiding machine to braid the treated copper fibers according to a preset density distribution map, wherein the high-density area uses thicker fibers and tight needle method for interweaving, and the low-density area uses thinner fibers and loose needle method for interweaving; During the braiding process, in the transition zone between the high-density area and the low-density area, the needle density is adjusted row by row and different diameter fibers are mixed to realize gradual change of the fiber network density and form a density transition zone; Place the braided fiber mesh preform into a special mold, apply different light pressure to the first area through a pre-pressing device to preliminarily stabilize its three-dimensional form and gradient density structure to form a fiber skeleton; Send the pre-pressed and shaped fiber skeleton into a protective atmosphere sintering furnace for annealing treatment to eliminate internal stress and improve the bonding strength of the fiber nodes, thereby obtaining an integrated copper fiber reinforced skeleton.
[0011] Optionally, the process of filling the three tin-based slurries into the preset areas of the hollow space gaps of the reinforced skeleton to form a gradient structure material specifically includes: Fix the copper fiber reinforced skeleton with a gradient density distribution in a filling mold, and the filling mold is provided with independently controllable inner layer area baffles, intermediate layer area baffles, and outer layer area baffles; Firstly, lower the inner layer area baffles, inject the inner layer slurry into the mold, and make the inner layer slurry fully fill the hollow space gaps in the inner layer area of the reinforced skeleton through vibration; After the inner layer slurry is preliminarily shaped, the inner layer area baffle is raised and the middle layer area baffle is lowered, the middle layer slurry is injected into the mold, and the slurry is filled in the middle area while forming a preliminary interface with the inner layer slurry by controlling the injection pressure; The middle layer area baffle is raised and the outer layer area baffle is lowered, the outer layer slurry is injected into the mold, and the outer layer area is fully filled under the condition of vacuum assistance, forming a gradient structure material.
[0012] Optionally, the gradient structure material is compression molded and post-processed to obtain a preformed solder, specifically including: The gradient structure material is subjected to cold isostatic pressing treatment, and the slurry of each layer is densified under a set pressure and holding time to obtain a composite green body with sufficient strength; The composite green body is placed in a gradient temperature field for sintering treatment, and the mutual diffusion of alloy elements is promoted by controlling the temperature of different areas to realize metallurgical bonding of the interlayer interface, and a sintered body is obtained; The sintered body is subjected to hot pressing densification treatment under a set temperature and pressure condition to eliminate internal pores, and a size-accurate gradient composite structure preformed solder is obtained through finishing.
[0013] Optionally, the composite green body is placed in a gradient temperature field for sintering treatment, and the mutual diffusion of alloy elements is promoted by controlling the temperature of different areas to realize metallurgical bonding of the interlayer interface, and a sintered body is obtained, specifically including: The composite green body is loaded into a special gradient sintering furnace bearing tray, and the gradient sintering furnace has an independently temperature-controlled outer layer heating area, a middle layer heating area and an inner layer heating area; Hydrogen protective gas is introduced into the sintering furnace, after the air in the furnace is removed, the heating system of each area is started, the temperature of the outer layer heating area is raised to 240-250℃, the temperature of the middle layer heating area is raised to 220-230℃, and the temperature of the inner layer heating area is raised to 200-210℃, forming a stable gradient temperature field; In the gradient temperature field, the alloy elements in the tin-based slurry of each layer are directionally diffused through the interlaced space of the copper fiber reinforced skeleton, and the metallurgical bonding of the interlayer interface is realized; After the holding sintering is completed, a partitioned step-down cooling method is adopted, and each area is controlled to be cooled to below 80℃ at a rate of not more than 5℃ / min, to obtain a sintered body with firm interface bonding and small internal stress.
[0014] This invention also provides a tin-based alloy preformed solder sheet, which is prepared by the tin-based alloy preformed solder sheet preparation method described above. The tin-based alloy preformed solder sheet includes a copper fiber reinforced skeleton and a three-layer structure composite therewith: an outer layer is a tin-antimony-copper-nickel high-hardness wear-resistant layer, a middle layer is a tin-antimony-copper transition layer, and an inner layer is a tin-antimony-copper high-toughness bonding layer; the three layers are metallurgically bonded to form a gradient structure with continuous transition of composition and performance, and the copper fiber reinforced skeleton runs through each layer to form a three-dimensional continuous network.
[0015] Compared with existing technologies, this invention has the following advantages: First, a copper fiber reinforced skeleton with hollow gaps and a gradient density distribution is constructed through a weaving process, serving as a three-dimensional support carrier; then, a high-hardness, wear-resistant outer layer slurry mainly composed of tin-antimony-copper-nickel, a transitional intermediate layer slurry mainly composed of tin-antimony-copper, and a high-toughness inner layer slurry mainly composed of tin-antimony-copper-rare earth are filled into the corresponding preset areas of the reinforced skeleton in a predetermined order to obtain a gradient filling structure with progressively changing composition and function; the gradient structure material is then pressed, molded, and post-processed to obtain a pre-formed solder sheet with integrated performance; this process, by first building the skeleton and then filling the material, with the copper fibers inside the solder sheet providing good support and thermal conductivity channels, achieves a gradient transition structure with continuously changing composition and performance, greatly enhancing the material's integrity, impact resistance, and bonding strength. Attached Figure Description
[0016] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0017] The structures, proportions, sizes, etc., shown in the accompanying drawings of this specification are only for the purpose of assisting those skilled in the art in understanding and reading the content disclosed in the specification, and are not intended to limit the conditions under which the present invention can be implemented. Therefore, they have no substantial technical significance. Any modifications to the structure, changes in the proportions, or adjustments to the size, without affecting the effects and objectives that the present invention can produce, should still fall within the scope of the technical content disclosed in the present invention.
[0018] Figure 1 This is a schematic flowchart of the preparation method of the tin-based alloy preformed solder sheet in this embodiment. Detailed Implementation
[0019] To make the objectives, features, and advantages of this invention more apparent and understandable, the technical solutions of the embodiments of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the embodiments described below are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0020] In the description of this invention, it should be understood that the terms "upper," "lower," "top," "bottom," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, and are only for the convenience of describing the invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of the invention. It should be noted that when a component is considered to be "connected" to another component, it can be directly connected to the other component or there may be a component positioned centrally in the connection.
[0021] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments.
[0022] Example 1: Combination Figure 1 As shown, this embodiment of the invention provides a method for preparing a tin-based alloy preformed solder sheet, comprising the following steps: S1, Prepare a copper fiber reinforced skeleton with a gradient density distribution. The copper fiber reinforced skeleton includes high-density regions and low-density regions, and is formed with hollow gaps through a weaving process.
[0023] By employing a weaving process to create high-density and low-density zones in the thickness direction and within the plane, while retaining perforations, the skeleton provides strong mechanical support in high-load or high-wear areas, and also provides space for the slurry in low-density areas to achieve interlayer transitions in composition and structure. The copper fiber skeleton forms a three-dimensional continuous network in the overall structure, which facilitates the diffusion and conduction of heat, electricity, and metallic elements during subsequent heat treatment, thereby promoting interlayer metallurgical bonding and improving the overall reliability and thermal conductivity of the composite.
[0024] S2, with an outer layer slurry based on tin, antimony, copper and nickel, an intermediate layer slurry based on tin, antimony and copper, and an inner layer slurry based on tin, antimony, copper and rare earth, tin-based slurries with different compositions and functions are prepared. The three tin-based slurries are then sequentially filled into the preset areas of the hollowed-out gaps of the reinforcing skeleton to form a gradient structure material.
[0025] It should be noted that by preparing three tin-based pastes with different functions (the outer layer is based on tin-antimony-copper-nickel, the middle layer is based on tin-antimony-copper, and the inner layer is based on tin-antimony-copper-rare earth) and filling them into the hollow space of the copper fiber skeleton in a predetermined manner, the composition can be continuously or stepwise transitioned with the thickness.
[0026] The different components of the slurry each serve different functions: the outer layer focuses on improving surface hardness and wear resistance, the middle layer serves as a buffer for mechanical and compositional transition, and the inner layer focuses on providing excellent bonding toughness and interfacial affinity; the gradient structure formed by the three can macroscopically balance wear resistance, strength and weldability, while enhancing the overall fracture resistance and heat transfer capacity through the interpenetrating structure with the skeleton.
[0027] The key to the partitioned filling process is to ensure that each layer of slurry fully wets the pores of the skeleton at its predetermined position and forms good contact between layers, so as to achieve directional diffusion and metallurgical bonding during subsequent heat treatment, thereby obtaining a gradient composite material with a smooth transition in composition and properties.
[0028] S3 involves pressing and molding the gradient structure material, followed by post-processing, to obtain a preformed weld sheet.
[0029] First, densification methods such as pressing or isostatic pressing are used to eliminate most of the loose porosity at the contact surfaces between each layer of slurry and the copper fiber skeleton, enhancing interfacial contact. Then, necessary heat treatments (such as sintering, diffusion treatment, and staged temperature control) promote diffusion and metallurgical bonding between the tin-based alloy and the skeleton at the interface, forming a strong interlayer bond and reducing internal stress. Finally, hot pressing or precision machining yields preformed solder sheets with precise dimensions and surface and internal structures that meet assembly / reflow soldering or other application requirements.
[0030] The working principle of this invention is as follows: First, a copper fiber reinforced skeleton with hollow gaps and a gradient density distribution is constructed through a weaving process, which serves as a three-dimensional support carrier. Then, a high-hardness and wear-resistant outer layer slurry mainly composed of tin-antimony-copper-nickel, a transitional intermediate layer slurry mainly composed of tin-antimony-copper, and a high-toughness inner layer slurry mainly composed of tin-antimony-copper-rare earth are filled into the corresponding preset areas of the reinforced skeleton in a set order to obtain a gradient filling structure with progressively changing composition and function. The gradient structure material is then pressed, molded, and post-processed to obtain a pre-formed solder sheet with integrated performance. This process, by first building the skeleton and then filling the material, with the copper fibers inside the solder sheet providing good support and thermal conductivity channels, achieves a gradient transition structure with continuously changing composition and performance, greatly enhancing the material's integrity, impact resistance, and bonding strength.
[0031] The three-dimensional interpenetrating network formed by the copper fiber skeleton and tin-based paste greatly enhances the integrity, impact resistance and bonding strength of the material, avoiding the interlayer delamination problem caused by abrupt changes in interface properties in multilayer materials.
[0032] In this embodiment, the outer slurry is composed of 60-70% tin, 12-14% antimony, 6-8% copper, 1-2% nickel, and 0.5-1.5% nano-alumina.
[0033] With tin as the base, the high content of antimony and copper imparts significant hardness and wear resistance to the outer layer, making it suitable as a working surface subjected to friction and mechanical contact. 1–2% nickel helps improve the alloy's mechanical strength, grain stability, and interfacial wettability with the copper-based framework, inhibiting the rapid growth of brittle phases along the interface. Nano-alumina, dispersed in the matrix as fine particles, further enhances wear resistance, inhibits grain growth, and improves thermal stability. Overall, the outer layer formulation significantly improves surface wear resistance and corrosion resistance while sacrificing some ductility, and forms a robust and durable protective layer through metallurgical bonding with the framework. In terms of process, densification and sintering temperature / time should be controlled to avoid the growth of excessive intermetallic compound layers, which could affect toughness.
[0034] In this embodiment, the intermediate layer slurry is composed of 75-82% tin, 8-10% antimony, 4-5% copper and 0.5-1% nickel.
[0035] The intermediate layer, with its high tin content, maintains a certain degree of ductility and plasticity. Serving as a transition layer between the high hardness of the outer layer and the high toughness of the inner layer, it functions as a stress transition and composition buffer. 8–10% antimony and 4–5% copper provide the intermediate layer with the necessary strength and wear resistance, while avoiding the brittleness of the outer layer; 0.5–1% nickel helps refine the microstructure and improve interfacial bonding. During heat treatment, this layer forms a robust metallurgical bond with the outer layer and, through its high tin content, absorbs thermal stress and plastic deformation, thereby reducing interfacial crack formation and ensuring the mechanical continuity of the gradient structure.
[0036] In this embodiment, the inner layer slurry is composed of 80-87% tin, 6-8% antimony, and 3-4% copper.
[0037] The inner layer maintains the highest tin content to ensure excellent solderability, bonding toughness, and ductility, providing good wettability and crack resistance as a bonding layer in contact with the workpiece or substrate. 6–8% antimony and 3–4% copper enhance the mechanical strength and fatigue resistance of the inner layer without significantly reducing ductility, enabling it to form reliable metallurgical bonds and withstand thermomechanical cycles. Since the inner layer directly participates in interfacial diffusion and bonding, the formulation is designed to suppress the excessive formation of brittle compounds, thus balancing bond strength and toughness, facilitating reliable bonding in subsequent reflow or hot-pressing processes.
[0038] In this embodiment, the specific process for preparing a copper fiber reinforced skeleton with a gradient density distribution is described as follows: S11. Prepare copper fiber raw materials of different diameters, and clean and roughen the surface of the pure copper fiber raw materials to enhance their bonding strength with the subsequent tin-based paste. The cleaning intensity and roughening depth need to be controlled during the process to avoid excessive corrosion that could lead to fiber breakage or reduction in cross-section. At the same time, the repeatability of the surface chemical state must be maintained to ensure consistent interfacial bonding performance between batches.
[0039] S12 uses a multi-arm braiding machine to weave the treated copper fibers according to a preset density distribution pattern. In the high-density area, thicker fibers are used and interwoven with a tight stitch, while in the low-density area, thinner fibers are used and interwoven with a loose stitch.
[0040] The treated copper fibers are woven into a mesh preform using a multi-arm braiding machine at a preset density distribution. The core of this process lies in achieving an orderly distribution of high-density and low-density zones through the matching of process parameters and fiber diameter. Specifically, thicker copper fibers are used in the high-density zones with a tighter weaving pattern (smaller stitch pitch, higher interlacing frequency) to obtain smaller pore sizes and higher local volume fractions; while finer fibers are used in the low-density zones with a looser weaving pattern to create greater porosity. Precise control of fiber tension, stitch pitch, and interlayer interlacing is crucial during weaving to ensure the skeleton's dimensions, pore connectivity, and local density match the design. Figure 1 To.
[0041] S13, during the weaving process, in the transition zone between high-density and low-density areas, by adjusting the needle density row by row and mixing in fibers of different diameters, a gradual change in fiber network density is achieved, forming a density transition zone.
[0042] By adjusting the needle density row by row and incorporating fibers of different diameters between high-density and low-density zones, a gradual transition zone is constructed. This zone eliminates stress concentration caused by abrupt interface changes and provides a smooth transition channel for the layered wetting of the sizing agent. Two methods can be employed: staggered blending (introducing fibers of different thicknesses simultaneously in the transition rows) and gradually tightening / loosening the needle to achieve a fiber network structure that gradually changes from dense to loose. Key process control points include the design of the transition zone width (to ensure a smooth mechanical gradient), the controllability of the fiber blending ratio, and online monitoring of local volume fraction after weaving to ensure that the transition zone achieves the desired effect both macroscopically and microscopically.
[0043] S14, the woven fiber mesh preform is placed into a special mold, and different light pressures are applied to the first area through a pre-compression device to initially stabilize its three-dimensional shape and gradient density structure to form a fiber skeleton.
[0044] The woven fiber mesh preform is placed into a specialized mold, and differentiated light pressure is applied to different areas using a pre-compression device to initially stabilize the three-dimensional morphology and fix the gradient density structure. The purpose of pre-compression is not complete densification but to eliminate obvious wrinkles, adjust interlayer thickness, maintain the predetermined outline of the skeleton, and improve dimensional consistency during subsequent grouting. This can be achieved using zoned, controllable pressure plates or pads, applying different compression amounts and holding times to the first area compared to other areas. Care must be taken to match the pressure level and compression rate in this step to avoid excessive tightness that could lead to local pore closure or fiber displacement, while maintaining sufficient pore connectivity to facilitate subsequent grout penetration.
[0045] S15, the pre-compressed fiber skeleton is sent into a protective atmosphere sintering furnace for annealing treatment to eliminate internal stress and improve the bonding strength of fiber nodes, thereby obtaining an integrated copper fiber reinforced skeleton.
[0046] The pre-compressed fiber skeleton undergoes annealing / sintering in a protective atmosphere to eliminate internal stresses introduced during manufacturing and strengthen the mechanical bonding of fiber nodes, thereby obtaining an integrated copper fiber reinforced skeleton. Annealing is typically performed in an inert gas or reducing protective atmosphere to prevent oxidation and may promote diffusion bonding or sintering neck growth at local metal contact surfaces, improving the bonding strength of nodes and thermal / electrical continuity. After treatment, the skeleton needs to be inspected for appearance and structure (e.g., porosity, local volume fraction, node strength, and shape stability).
[0047] In this embodiment, step S2 specifically includes: S21, a copper fiber reinforced skeleton with gradient density distribution is fixed in a filling mold, the filling mold is provided with an inner layer region baffle, a middle layer region baffle and an outer layer region baffle that can be controlled independently.
[0048] It should be noted that fixing the prepared gradient density copper fiber reinforced skeleton in a zoned and controllable filling mold aims to precisely position the skeleton and provide a sealed and isolated working space for layered pouring. The mold should have three independently adjustable baffles (inner / middle / outer layer) and reliable sealing surfaces to prevent the slurry from flowing in unwanted directions or mixing during filling. Simultaneously, the mold design must include overflow and venting channels to allow for excess slurry and gas discharge. The fixing process must ensure the flatness and layer thickness consistency of the skeleton (using fixing clamps or light pressure plates), and the mold cavity surface should be cleaned and treated with a release agent to improve filling quality and repeatability. Before operation, the sealing and positioning accuracy of the baffles should be checked to avoid interlayer defects caused by slurry leakage or misalignment in the mold.
[0049] S22, first lower the inner layer area baffle, inject the inner layer slurry into the mold, and use vibration to make the inner layer slurry fully fill the hollow space gap of the inner layer area of the reinforcing skeleton.
[0050] First, lower the inner layer baffle and inject the inner layer slurry. Use vibration or ultrasound to help the slurry fully penetrate and fill the pores in the inner layer of the skeleton. The purpose is to ensure that the inner layer slurry forms a continuous wetting phase within the micropores and expels air. After injection and vibration, a short period of static or preliminary curing treatment (such as temperature control or drying methods) should be performed to form a preliminary sizing layer and provide a stable substrate for subsequent layers.
[0051] S23. After the inner layer slurry has initially set, raise the inner layer area baffle and lower the middle layer area baffle, inject the middle layer slurry into the mold, and control the injection pressure so that the slurry forms a preliminary interface bond with the inner layer slurry while filling the middle area.
[0052] Once the inner layer slurry has reached initial set (sufficient to prevent excessive flow), raise the inner layer baffle and lower the middle layer baffle, injecting the middle layer slurry into the mold. By precisely controlling the injection pressure and rate, the middle layer slurry achieves sufficient contact with the set inner layer slurry at the interface during filling, preventing large-scale miscibility and thus forming a preliminary interfacial bond. The key to this process lies in matching the rheological properties of the two slurries (avoiding excessive fluidity of the middle layer that could erode the inner layer) and appropriately setting the injection pressure and the timing of the baffle raising and lowering. If necessary, low-pressure multi-point injection or gradient pressure injection can be used to ensure uniform filling. After injection, a brief stabilization and degassing period should be performed to reduce interfacial porosity and observe for any obvious interfacial unevenness or delamination.
[0053] S24, raise the baffle of the middle layer area and lower the baffle of the outer layer area, inject the outer layer slurry into the mold, and complete the full filling of the gaps in the outer layer area under vacuum assistance to form a gradient structure material.
[0054] After a stable initial interface is formed between the intermediate and inner layers, the intermediate layer baffle is raised and the outer layer baffle is lowered. The outer layer slurry is then injected, and under vacuum assistance, the outer layer region and the fine pores on the surface are fully filled. Vacuum assistance helps remove residual gas, improves the wettability of the slurry to fine pores, and prevents the formation of closed-cell bubbles on the surface and inside. Simultaneously, the outer layer often requires high filling uniformity to meet wear resistance and surface densification requirements. Key control points include degassing of the outer layer slurry, coordination between injection speed and vacuum level (avoiding slurry boiling or bubble expansion under extremely high vacuum), and appropriate backpressure or holding pressure processes after injection to stabilize the interface.
[0055] In this embodiment, step S3 specifically includes: S31 involves cold isostatic pressing of the gradient structure material to densify each layer of slurry within a set pressure and holding time, thereby obtaining a composite green body with sufficient strength.
[0056] Cold isostatic pressing is a process in which a filled and preliminarily shaped gradient structural material is placed in an isostatic pressing vessel at room temperature, and the isotropic pressure of a liquid medium (usually oil or a water-glycerol mixture) simultaneously densifies each layer of the slurry. The main purpose of this step is to eliminate large-sized interconnected pores, increase the contact area between each layer and the copper fiber skeleton, and obtain a composite green body with sufficient mechanical strength, facilitating subsequent mounting and heat treatment.
[0057] S32 involves placing the composite green billet in a gradient temperature field for sintering. By controlling the temperature in different regions, the mutual diffusion of alloying elements is promoted, achieving metallurgical bonding at the interlayer interface and obtaining a sintered body. The composite green compact is placed in a gradient sintering furnace with independent temperature control zones. Under a protective atmosphere (such as hydrogen or inert gas), a stable gradient field with different temperatures at the outer, middle, and inner layers is formed through zoned heating. This temperature difference drives the directional diffusion of alloying elements between layers, achieving metallurgical bonding. According to the process description of this embodiment, the outer layer can be heated to approximately 240–250°C, the middle layer to approximately 220–230°C, and the inner layer to approximately 200–210°C, and held for 60–90 minutes. This temperature gradient promotes interdiffusion of elements between layers to form a continuous bonded phase while inhibiting excessive formation of brittle intermetallic compounds. Key points in the sintering process include strict atmosphere control to prevent oxidation, precise temperature zoning and heating / cooling rates to avoid thermal stress concentration, and optimization of holding time and temperature to control interface thickness and phase composition while meeting interfacial bonding strength requirements. After sintering, zoned step cooling is used with a controlled cooling rate (e.g., no more than 5°C / min) to reduce internal stress and prevent crack formation.
[0058] S33 involves hot-pressing densification of the sintered body to eliminate internal pores under set temperature and pressure conditions, and then obtaining a dimensionally precise gradient composite preform through precision machining.
[0059] Hot pressing densification of sintered bodies is a key step in further eliminating residual porosity and improving densification under controlled temperature and pressure conditions. Hot pressing typically applies external pressure at a temperature slightly higher than the sintering temperature or at a temperature that activates plastic flow. This causes the matrix material to fill micropores under high temperature and high stress coupling, promoting limited plastic flow and recrystallization at the interfaces, thereby significantly improving bulk density and interfacial bonding strength. Process design requires balancing temperature, pressure, and holding time: excessively high temperatures and times can promote the growth of brittle phases and impair weldability, while excessive pressure can damage the skeleton structure or cause interlayer extrusion; therefore, optimal parameters must be determined experimentally and real-time temperature / displacement monitoring must be performed.
[0060] In this embodiment, step S32 specifically includes: S321, the composite green body is loaded into the support tray of a special gradient sintering furnace, which has an independently temperature-controlled outer heating zone, a middle heating zone and an inner heating zone.
[0061] The purpose of loading composite green bodies into the support trays of a dedicated gradient sintering furnace is to ensure precise and repeatable positioning of the workpieces within the zoned temperature control field through tray positioning and layout. The support trays should be resistant to hydrogen and process temperatures, possess good thermal conductivity and dimensional stability, and have pre-reserved placement positions on them according to an outer-middle-inner three-zone design to ensure each piece is within its corresponding heating zone. Simultaneously, reasonable spacing on the trays facilitates gas flow and temperature uniformity. To achieve precise temperature control, several thermocouples or temperature sensors should be placed near the trays and green bodies for online feedback control. Furthermore, the tray fixing structure must be able to withstand thermal expansion during heating to prevent workpiece displacement or contact that could lead to localized abnormal heat transfer.
[0062] S322, hydrogen protective gas is introduced into the sintering furnace to purge the air inside the furnace, and then the heating systems of each zone are started to raise the temperature of the outer heating zone to 240-250℃, the temperature of the middle heating zone to 220-230℃, and the temperature of the inner heating zone to 200-210℃, forming a stable gradient temperature field.
[0063] Hydrogen protective gas is introduced into the sintering furnace while air is fully purged. This provides a reducing / inert atmosphere during the heating and high-temperature stages to prevent oxidation of the copper fibers and tin-based paste surfaces. Simultaneously, hydrogen can promote the reduction of surface oxides to some extent, improving interfacial wettability. After replacement, each heating zone is activated, raising the outer, middle, and inner layers to the specified temperatures of 240–250℃, 220–230℃, and 200–210℃, respectively, to create a stable gradient temperature field.
[0064] S323 is sintered at a gradient temperature field for 60-90 minutes, allowing alloying elements in each layer of tin-based paste to diffuse directionally through the gaps in the copper fiber reinforced skeleton, thus achieving metallurgical bonding at the interlayer interface.
[0065] After establishing a stable temperature gradient field, the composite green compact is held at temperature for 60–90 minutes. This allows the different temperature conditions at the outer, middle, and inner layers to promote the directional diffusion of alloying elements such as tin, antimony, copper, and nickel along the temperature gradient. Interdiffusion of elements occurs through the hollow channels of the copper fiber skeleton, forming a metallurgical bonding zone between the layers. The holding time and temperature together determine the interfacial diffusion depth and phase composition, requiring optimization to achieve both reliable metallurgical bonding and the suppression of excessively thick brittle phase layers. During the holding period, a stable atmosphere should be maintained, temperature deviations should be monitored regularly, and vibration or workpiece compression should be avoided to ensure the uniformity of the interfacial microstructure and the achievement of mechanical property targets.
[0066] S324, after heat preservation sintering, adopts a zoned step cooling method to control each area to be cooled synchronously to below 80°C at a rate of no more than 5°C / minute, so as to obtain a sintered body with strong interface bonding and low internal stress.
[0067] After the heat preservation period, a zoned, stepped cooling method is adopted, controlling each zone to cool synchronously to below 80°C at a rate not exceeding 5°C / minute. The purpose is to reduce thermal stress generation through a controllable cooling rate and avoid interface cracks or warping caused by sudden cooling. Zoned, stepped cooling allows the temperature to gradually converge while maintaining the temperature difference between zones. Combined with uniform airflow in the furnace and heat conduction through the trays, this enables the multi-layered structure to gradually undergo controlled thermal contraction during the cooling process, reducing residual stress. The temperature curve should also be monitored during the cooling process, and the slow cooling section should be appropriately extended in critical temperature ranges (such as the phase transformation zone) to ensure the stability of the interfacial phase structure and ultimately obtain a sintered body with strong interfacial bonding and low internal stress.
[0068] Example 2: A tin-based alloy preformed solder sheet is prepared using the method described in Example 1. The tin-based alloy preformed solder sheet includes a copper fiber reinforced skeleton and a three-layer structure composite therewith: an outer layer is a tin-antimony-copper-nickel high-hardness wear-resistant layer, a middle layer is a tin-antimony-copper transition layer, and an inner layer is a tin-antimony-copper high-toughness bonding layer. The three layers are metallurgically bonded to form a gradient structure with continuous transition in composition and performance, and the copper fiber reinforced skeleton runs through each layer to form a three-dimensional continuous network.
[0069] The above-described embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a tin-based alloy preformed solder sheet, characterized in that, Includes the following steps: A copper fiber reinforced skeleton with a gradient density distribution is prepared, the copper fiber reinforced skeleton including a high-density region and a low-density region, and is formed with hollow gaps by a weaving process; A tin-based slurry with different components and functions is prepared by using an outer slurry with tin, antimony, copper and nickel as the main components, an intermediate slurry with tin, antimony and copper as the matrix, and an inner slurry with tin, antimony, copper and rare earth as the matrix. The three tin-based slurries are then sequentially filled into the preset area of the hollow space of the reinforcing skeleton to form a gradient structure material. The gradient structure material is press-formed and post-processed to obtain a preformed weld sheet.
2. The method for preparing tin-based alloy preformed solder sheets according to claim 1, characterized in that, The outer slurry is composed of 60-70% tin, 12-14% antimony, 6-8% copper, 1-2% nickel, and 0.5-1.5% nano-alumina.
3. The method for preparing tin-based alloy preformed solder sheets according to claim 1, characterized in that, The specific composition of the intermediate layer slurry is: 75-82% tin, 8-10% antimony, 4-5% copper and 0.5-1% nickel.
4. The method for preparing tin-based alloy preformed solder sheets according to claim 1, characterized in that, The inner layer slurry is composed of 80-87% tin, 6-8% antimony, and 3-4% copper.
5. The method for preparing tin-based alloy preformed solder sheets according to claim 1, characterized in that, The specific process for preparing a copper fiber reinforced skeleton with a gradient density distribution is as follows: Prepare copper fiber raw materials of different diameters, and clean and roughen the surface of the pure copper fiber raw materials. Using a multi-arm braiding machine, the treated copper fibers are braided according to a preset density distribution diagram. In the high-density area, thicker fibers are used and interwoven with a tight stitch, while in the low-density area, thinner fibers are used and interwoven with a loose stitch. During the weaving process, in the transition zone between high-density and low-density areas, the density of the fiber network is gradually changed by adjusting the needle density row by row and mixing in fibers of different diameters, thus forming a density transition zone. The woven fiber mesh preform is placed into a special mold, and different light pressures are applied to the first area through a pre-compression device to initially stabilize its three-dimensional shape and gradient density structure to form a fiber skeleton. The pre-compressed fiber skeleton is sent to a protective atmosphere sintering furnace for annealing to eliminate internal stress and improve the bonding strength of fiber nodes, thereby obtaining an integrated copper fiber reinforced skeleton.
6. The method for preparing tin-based alloy preformed solder sheets according to claim 1, characterized in that, The step of sequentially filling three tin-based pastes into a predetermined region of the hollowed-out gaps in the reinforcing skeleton to form a gradient structure material specifically includes: The copper fiber reinforced skeleton with gradient density distribution is fixed in a filling mold, which is provided with an inner layer baffle, a middle layer baffle and an outer layer baffle that can be controlled independently. First, lower the inner layer baffle, inject the inner layer slurry into the mold, and use vibration to make the inner layer slurry fully fill the hollow space of the inner layer area of the reinforcing skeleton. After the inner layer slurry has initially set, the inner layer area baffle is raised and the middle layer area baffle is lowered. The middle layer slurry is then injected into the mold. By controlling the injection pressure, the slurry fills the middle area while forming a preliminary interface with the inner layer slurry. Raise the baffle plate in the middle layer area and lower the baffle plate in the outer layer area, inject the outer layer slurry into the mold, and fully fill the gaps in the outer layer area under vacuum-assisted conditions to form a gradient structure material.
7. The method for preparing tin-based alloy preformed solder sheets according to claim 1, characterized in that, The gradient structure material is press-formed and post-processed to obtain a preformed weld sheet, specifically including: The gradient structure material is subjected to cold isostatic pressing to densify each layer of slurry under a set pressure and holding time to obtain a composite green body with sufficient strength. The composite green body is placed in a gradient temperature field for sintering. By controlling the temperature in different regions, the mutual diffusion of alloying elements is promoted, and metallurgical bonding of the interlayer interface is achieved to obtain a sintered body. The sintered body is subjected to hot pressing densification treatment to eliminate internal pores under set temperature and pressure conditions, and then a dimensionally accurate gradient composite structure preform is obtained through precision machining.
8. The method for preparing tin-based alloy preformed solder sheets according to claim 1, characterized in that, The composite green body is sintered in a gradient temperature field. By controlling the temperature in different regions, the interdiffusion of alloying elements is promoted, achieving metallurgical bonding at the interlayer interfaces to obtain a sintered body. Specifically, this includes: The composite green body is loaded into the support tray of a dedicated gradient sintering furnace, which has an independently temperature-controlled outer heating zone, a middle heating zone, and an inner heating zone. Hydrogen protective gas is introduced into the sintering furnace to purge the air inside the furnace. Then, the heating systems of each zone are started to raise the temperature of the outer heating zone to 240-250℃, the temperature of the middle heating zone to 220-230℃, and the temperature of the inner heating zone to 200-210℃, forming a stable gradient temperature field. The alloying elements in each layer of tin-based paste are sintered at the gradient temperature field for 60-90 minutes, allowing them to diffuse directionally through the gaps in the copper fiber reinforced skeleton, thus achieving metallurgical bonding at the interlayer interface. After the heat preservation sintering is completed, a zoned step cooling method is adopted to control each area to cool synchronously to below 80°C at a rate of no more than 5°C / minute, so as to obtain a sintered body with strong interface bonding and low internal stress.
9. A tin-based alloy preformed solder sheet, characterized in that, The tin-based alloy preformed solder sheet is prepared by the preparation method of any one of claims 1 to 8. The tin-based alloy preformed solder sheet includes a copper fiber reinforced skeleton and a three-layer structure composite therewith: an outer layer is a tin-antimony-copper-nickel high-hardness wear-resistant layer, a middle layer is a tin-antimony-copper transition layer, and an inner layer is a tin-antimony-copper high-toughness bonding layer; the three layers are metallurgically bonded to form a gradient structure with continuous transition of composition and performance, and the copper fiber reinforced skeleton runs through each layer to form a three-dimensional continuous network.
Citation Information
Cited By
Composite electric contact material, preparation method and electric contact element
CN121617834A
Method for preparing copper fiber reinforced tin-based composite soldering sheet by large deformation rolling
CN122462777A